1996
DOI: 10.1123/jsep.18.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscular Activity while Imagining Weight Lifting Using Stimulus or Response Propositions

Abstract: Investigating emotional imagery, Lang (1977Lang ( , 1979 proposed a dichotomy between stimulus and response propositions. In this study, Lang's model is applied to movement images of lifting of 4.5 and 9 kg weights. Twenty-two male and 17 female students participated in the study. During the imaginary lifting of the weights, the electromyographical activity (EMG) of both biceps brachii muscles were assessed. Imagery ability was measured with the Movement Imagery Questionnaire (MIQ) and another self-report rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 25 publications
9
43
0
Order By: Relevance
“…First, our results support the previous findings by Bakker et al (1996) and Boschker (2001) who found that the MI of lifting 9 kg weights resulted in a larger EMG activity in the active arm than the MI of lifting 4 kg 1/2. In the present study, the MI of a heavy concentric contraction (80% of 1RM) resulted in a greater pattern of EMG activity than during MI of a light concentric condition (50% of 1RM).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…First, our results support the previous findings by Bakker et al (1996) and Boschker (2001) who found that the MI of lifting 9 kg weights resulted in a larger EMG activity in the active arm than the MI of lifting 4 kg 1/2. In the present study, the MI of a heavy concentric contraction (80% of 1RM) resulted in a greater pattern of EMG activity than during MI of a light concentric condition (50% of 1RM).…”
Section: Discussionsupporting
confidence: 94%
“…The antagonists which show eccentric activity have often been found activated during MI (e.g. Bakker et al, 1996;Boschker, 2001;Slade et al, 2002). Interestingly, the synergists and the muscles with a fixation function, eliciting single muscle action to reinforce the agonist activity and concerted activation of several muscles respectively, were also activated during MI, in our experiment.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, Bakker et al (1996) reported that muscle activity was higher in the active than in the passive arm during MI of arm movements, and that imagining lifting a heavy object resulted in greater electromyographic activity than lifting a lighter object. Interestingly, Guillot et al (2007) showed that this subliminal activity was specific to the type of muscle contraction the participants were requested to imagine, that is, concentric or eccentric muscle contraction.…”
Section: Introductionmentioning
confidence: 97%
“…49,50 However, the relationship between muscle strength and motor imagery is controversial in the literature. Although some studies underline the efficacy of motor imagery on muscle strength, 51,52 others report no increase in muscle strength. 53,54 In the present study, grip strength was found in similar degrees in both groups at the end of the eighth week.…”
Section: Discussionmentioning
confidence: 99%